2021
DOI: 10.18280/ijdne.160609
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Antifeedant Activity of Calotropis gigantea L. Leaf Extract Against Plutella xylostella L. (Lepidoptera: Plutellidae)

Abstract: Many parts of the Calotropis gigantea plant are known to contain bioactive compounds, but leaves contain the most. This study aimed to determine the toxicity and antifeedant activity of C. gigantea leaves against Plutella xylostella. The study was carried out from November 2019 to July 2020. Toxicity was tested using the leaf dipping and spraying methods. Antifeedant activity was tested using a no-choice test and a choice test. Identification of the compound composition of the leaf extract of C. gigantea was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(46 reference statements)
1
4
0
1
Order By: Relevance
“…This study was conducted during the rainy seasonis and it is estimated that the level of S. exigua infestation would be higher if the experiment were carried out in the dry season because no weather factors can prevent adults from laying their eggs to develop into larvae. This is per previous research found that the number of egg and larva populations [1], and imago [17] of S.exigua on shallots is much higher in the dry season than in the rainy season. Usually, after hatching from the egg, the young caterpillar immediately makes a hole at the tip of the leaf and then enters the leaf, so that the tip of the leaf appears hollow or cut.…”
Section: Discussionsupporting
confidence: 84%
“…This study was conducted during the rainy seasonis and it is estimated that the level of S. exigua infestation would be higher if the experiment were carried out in the dry season because no weather factors can prevent adults from laying their eggs to develop into larvae. This is per previous research found that the number of egg and larva populations [1], and imago [17] of S.exigua on shallots is much higher in the dry season than in the rainy season. Usually, after hatching from the egg, the young caterpillar immediately makes a hole at the tip of the leaf and then enters the leaf, so that the tip of the leaf appears hollow or cut.…”
Section: Discussionsupporting
confidence: 84%
“…The highest total content of the alkaloid group of tannins, phenols, flavonoids, and saponins was V. negundo extract, followed by A. conizoydes and C. gigantea leaf extracts. The same content of C. gigantea extract compounds as A. conizoydes is toxic and antifeedant against P. xylostella [24], has antifeedant properties against H. armigera [46], is toxic and antifeedat against S. exigua [47], while the compounds in the extract of V. negundo are repellent, antifeedant and toxic to Helicoverpa armigera. S. litura and Athalia proxima lugens [48].…”
Section: Group Of Leaf Extract Compounds V Negundo a Conizoydes And C...mentioning
confidence: 96%
“…At high concentrations, the three extracts with each concentration resulted in lower feed consumption by larvae resulting in an increase in the antifeedant index, while a decrease in the concentration of the treated extracts led to an increase in feed consumption by larvae, resulting in a decrease in the antifeedant index. According to Arivoli and Tennyson [38] and Khasanah et al [24], a high value of the antifeedant index indicates a decrease in food consumption by the test insects, and vice versa a decrease in the antifeedant index indicates a decrease in antifeedant activity.…”
Section: Antifeedant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Saponins and tannins are some of the components of complex organic substances known as secondary metabolites [2], [6]. Saponins are compounds that produce antimicrobial and antibacterial activity, which can help to lower blood cholesterol.…”
Section: Introductionmentioning
confidence: 99%